Social Change, Gender Stratification and the Sex Gap of Homicide Victimization in 76 Countries, 1975–2017 - Lu, Yunmei (The British journal of criminology, 2023)
This study examines the longitudinal change in the sex gap of homicide victimization in 76 countries between 1975 and 2017. We compiled a cross-national dataset with homicide victimization data from WHO and structural measures from multiple databases. Our findings reveal that countries with low homicide rates and rapid homicide decline are more likely to have narrowing sex gaps, and that the narrowing gaps are mainly driven by male homicide decline. Different from the prior literature, we find null associations between most measures of gender stratification and the sex gap. Instead, results reveal that aging population is associated with a narrowing sex gap. Implications are discussed, including the specific effects of the study period and the shifting dynamics of homicide trends.